Imatinib Mesylate Treatment in Chronic Myeloid Leukemia - Demet Çekdemir; Mehmet Gunduz (Sakarya Tıp Dergisi, 2020)
Objective: To evaluate retrospectively the efficacy of treatment in chronic myeloid leukemia (CML) patients followed up in our center and receiving imatinib treatment.Materials and Methods: Eighty-five chronic phase CML patients with adequate clinical and laboratory data were included in the study. These patients had not given hematological or cytogenetic responses after interferon treatment, or had intolerance to IFN treatment or received imatinib treatment as a first-line treatment in late and early chronic stage patients.Results: Forty-eight (56.5%) patients were male and 37 (43.5%) of them were female. The median age at diagnosis was 52 years (19-79). The mean follow-up period was 45 (12-158) months. In the follow-up, 6 of the chronic phase patients progressed to blastic and accelerated phase. In the third month of imatinib treatment, 77 (90.6%) patients had complete hematologic response and 85 (100%) patients had full hematologic response at 18 months. In our study, cytogenetic data of 78 patients with adequate metaphase (≥ 20) could be evaluated within the first 18 months after the diagnosis was made. At the end of 18 months, 68 (87.2%) of 78 patients had complete cytogenetic response.